The Effect of Shopee’s Twin Date Campaign on Impulsive Buying: The Mediating Role of FOMO and Moderating Self-Control - Yusrilzal Rokhim; Yoma Bagus Pamungkas; Edi Nurwahyu Julianto (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to examine the effect of Shopee's Twin Date Campaign on impulsive buying, focusing on the mediating role of fear of missing out and the moderating role of self-control. This study uses four theories, namely Elaboration Likelihood Model Theory, Social Comparison Theory, Ego Depletion Theory, and Cognitive Emotional Theory, involving 384 respondents, according to Lemeshow's formula. The criteria for respondents were active users of Shopee and social media in Indonesia during the Shopee Twin Date Campaign. The method used in this study was Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS Version 4 software. Based on the findings, the Shopee Twin Date Campaign significantly and positively influenced Impulsive Buying alongside Fear of Missing Out. It further emerged that Fear of Missing Out mediates the Shopee Twin Date Campaign and Impulsive Buying relationship, while Self-control also emerged as a significant moderator.. These findings support to the development of digital marketing communication with a focus on psychological mechanisms in driving consumer behavior. In addition, this study can also be a reference for e-commerce industry developers and policymakers to design more responsible campaigns that take consumer literacy into consideration.